The Mediating Role of The Meaning of Life in the Effect of Spiritual Well-Being on Post-Traumatic Growth During the Covid-19 Pandemic Process - ERMİŞ, ECE NAZ (Halil Ekşi, 2023)
Considering the effects of the COVID-19 epidemic on mental health, it has been determined that there is a need to focus on the positive parts of the post-traumatic results of the pandemic together with spiritual concepts. For this purpose, the mediating role of the meaning of life in the effect of spiritual well-being on post-traumatic growth during the Covid-19 pandemic process was examined. Within the scope of this general purpose: (a) the moderator role of fear of COVID in the mediating role of the meaning of life in the effect of mental well-being on post-traumatic growth, (b) the mediator role of the meaning of life in the effect of existential regret on post-traumatic growth were examined. The participants in the study consisted of 398 people, 263 women and 135 men, between the ages of 18-62. Data analysis includes correlation and regression analysis. As a result of the analyzes, it was observed that spiritual well-being had a statistically significant and positive effect on post-traumatic growth and the meaning of life had a partial mediating role in this relationship. While the effect of spiritual well-being on the meaning of life is at a significant level, it is observed that the fear of covid has a regulatory role in this effect. In addition, while the meaning of life has a significant effect on post-traumatic growth, it is also seen that existential regret has a regulatory role in this effect. It is thought that this study will provide functional evidence for the post-traumatic growth effects of the COVID-19 outbreak and for possible subsequent outbreaks.
Keywords: Covid-19; Meaning of Life; Post Traumatic Growth; Spiritual Well-Being